Microstructure and fracture behavior of polypropylene/nanoclay composites - Chen, Ling. (2008)
Maleic anhydride modified polypropylene (MAPP) was compounded with commercially available surface modified montmorillonite in a twin screw extruder. Re-compounding ensured the removal of visible tactoids from extrudable while TEM and WAXD techniques showed non-uniform dispersion of clay platelets, however, quite a few nanometer-thick clay layers can be identified.